Pengaruh Ukuran Perusahaan Likuiditas dan Profitabilitas terhadap Pengungkapan Islamic Social Reporting dengan Leverage sebagai Variabel Moderasi - Zuhriyanto, Zuhriyanto; Haryono, Slamet (Jurnal Magister Ekonomi Syariah, 2022)
This study aims to determine whether firm size affects the disclosure of Islamic social reporting, whether liquidity affects the disclosure of Islamic social reporting, and whether profitability affects the disclosure of Islamic social reporting. Then the researcher adds leverage as a moderating variable in the study that can moderate firm size, liquidity and profitability on Islamic social reporting disclosure of Islamic commercial banks in Indonesia. By using disclosure theory which shows that CSR disclosure which is modified into ISR is related to future financial performance and has a good influence on the financial performance of the instution in the long term.